2008
DOI: 10.1373/clinchem.2007.097469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homocysteine Concentration in Early Pregnancy on Gestational Hypertensive Disorders and Other Pregnancy Outcomes

Abstract: Background: Increased total homocysteine (tHcy) may be associated with placental-mediated adverse pregnancy outcomes, but few prospective studies have measured tHcy before pregnancy outcome. This study was undertaken to determine whether increased tHcy measured in early pregnancy is associated with pregnancy loss, gestational hypertension (GH), preeclampsia, or small for gestational age (SGA) infants. Methods: We conducted a prospective cohort study between 2002 and 2005. We measured tHcy and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 31 publications
1
82
1
8
Order By: Relevance
“…Some studies showed that hyperhomocysteinemia in early pregnancy can increase the risk of developing of preeclampsia 7,16,17 . In contrast, other studies detected no differences in midtrimester maternal circulating level of homocysteine between women who developed preeclampsia and normal pregnant women 15,[18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that hyperhomocysteinemia in early pregnancy can increase the risk of developing of preeclampsia 7,16,17 . In contrast, other studies detected no differences in midtrimester maternal circulating level of homocysteine between women who developed preeclampsia and normal pregnant women 15,[18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…24 Gestational age was confirmed using last menstrual period or ultrasound estimates. Blood samples were collected from October 2002 …”
Section: Cohort Design Participant Recruitment and Blood Collectionmentioning
confidence: 99%
“…Its alleles with C677/T677 or alanine 222 to valine substitutions are highly represented in the Caucasian population (Frosst et al 1995). This mutation is associated with thermolability and lower catalytic activity of MTHFR, elevated Hcy, and increased risk of obstetrical pathologies (De Franchis et al 1995, Shields et al 1999, Van der Put et al 2001, Dodds et al 2008. Regarding Hcy in pregnancy, numerous questions and problems remain unanswered such as the specific input of each organ or different stages of the folate-related metabolism into the integral value of Hcy concentrations in plasma and the particular role of the placenta in the overall folate-related metabolism in mother and fetus.…”
Section: Introductionmentioning
confidence: 99%